Seriös : Tentoonstellingen 1988. - Reiff, Wanda; Galerie Wanda Reiff, Maastricht (Maastricht : Galerie Wanda Reiff, 1988)
Bömmels, Peter ; Slits, Ton ; Wehrens, Peter ; Lafontaine, Marie-Jo ; Wilding, Alison ; Dumas, Marlene ; Knap, Jan ; Plug, Marian ; Dwurnik, Edward ; Herold, Georg ; Visser, Carel ; Messager, Annette ; Lavier, Bertrand ; Boltanski, Christian ; Claessen, Wim ; Garcia Sevilla, Ferran ; Vugs, Joop ; Nijman, Erna ; Droese, Felix ; Hulsteijn, Henk
boek